ANALISIS PENDIDIKAN KEWIRAUSAHAAN DALAM MENUMBUHKAN KETERAMPILAN BERFIKIR KRITIS DAN BERFIKIR KREATIF PADA SISWA SEKOLAH DASAR - Fitriani, Ari Deca; Sentosa, Sedya; Anriani, Titi; Khoirunnisa Salkeri, Fadiah; Ramaputri Tilotama, Azzahrah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Entrepreneurship education at the Elementary School level plays a strategic role in shaping the character and skills of the 21st century, especially in terms of critical and creative thinking. This article aims to analyze how entrepreneurship education can be applied as a learning tool that encourages students to be able to identify problems, formulate solutions, and generate new ideas independently and innovatively. Through a literature study approach and concept analysis, it was found that the integration of entrepreneurship education in the learning process can foster a solution-oriented, adaptive mindset, and encourage independence and responsibility from an early age. Project-based learning, business simulations, and thematic approaches are effective strategies in instilling a creative and critical entrepreneurial spirit. Therefore, entrepreneurship education needs to be continuously strengthened in elementary schools as an effort to prepare the younger generation who have intellectual, emotional, and social readiness to face future challenges. Entrepreneurship education is not only oriented towards the formation of an entrepreneurial spirit, but also becomes a means to develop students' critical and creative thinking skills from an early age. This article discusses "Analysis of Entrepreneurship Education in Cultivating Critical and Creative Thinking Skills in Elementary School Students". With a literature analysis approach from various theoretical sources and practices in the field, it was found that the application of entrepreneurship-based learning such as mini projects, simple business simulations, and exploratory activities was able to stimulate students' reasoning and creativity. Entrepreneurship education at the elementary level is an important part of creating a generation that is not only academically intelligent, but also resilient, independent, and able to compete creatively in the future.